A model for concepts extraction and context identification in knowledge based systems - Bortolon, Andre (2006)
Information Retrieval Systems normally deal with keywordbased technologies. Although those systems reach satisfactory results, they aren’t able to answer more complex queries done by users, especially those directly in natural language. To do that, there are the KnowledgeBased Systems, which use ontologies to represent the knowledge embedded in texts. Currently, the construction of ontologies is based on the participation of three components: the knowledge engineer, the domain specialist, and the system analyst. This work demands time due to the various studies that should be made do determine which elements must participate of the knowledge base and how these elements are interrelated. In this way, using computational systems that, at least, accelerate this work is fundamental to create systems to the market. A model, that allows a computer directly represents the knowledge, just needing a minimal human intervention, or even no one, enlarges the range of domains a system can maintain, becoming it more efficient and userfriendly.